Infrastructure-assisted joint power adaptation and routing for heterogeneous vehicular networks. (January 2019) - Hameed Mir, Zeeshan; Ko, Young-Bae; Filali, Fethi; Kim, Jaebeom
Abstract: In vehicular networks, protocols and algorithms rely on the in-network status information and its delivery via control messages for their operations. Using the same wireless channel for data and control message transmissions consume significant channel capacity and time, thus resulting in performance degradation. In this paper, a multi-tiered, heterogeneous vehicular network architecture is considered consisting of mainly two radio access technologies, i.e., ad hoc and cellular. Based on the concept of infrastructure-assistance, we suggested offloading control messages over the cellular network and data over the ad hoc network. Next, an efficient broadcast algorithm is proposed that exploits predicted connectivity information to decide on transmit power levels for each vehicle. Finally, a joint transmit power adaptation, and routing algorithm is implemented to disseminate data over a multi-hop network. Through extensive simulations, we reported significant performance gains in terms of delay, collision rate, and packet delivery ratio while maintaining lower communication overhead.